Making a budget - Uhl, Xina M.; Peterson, Judy Monroe (Uhl, Xina M. Managing your money and finances., 2020)
Teaches readers about how to make and stick to a budget. Discusses issues such as tracking income and expenses, evaluating a budget, saving, and spending. Includes a glossary, sources for further research, and an index.